Strengthening digital-based ecotourism through the development of iconic spots in Selorejo Village, Malang Regency - Vika Annisa Qurrata; Ermita Yusida; Vidya Purnamasari (University of Merdeka Malang, 2022)
Community service activities in the form of strengthening digital ecotourism through iconic spots are carried out to increase tourists' numbers, mostly visits by the millennial generation, which are identical to selfies and social media. This activity is intended for managers and the community of Wana Wisata Bedengan, which are located in Selorejo Village, Malang Regency, totaling ten people. Activities were carried out by using the Focus Group Discussion method to socialize and prepare for development, then assist in implementing the construction of iconic photo spots and evaluation of the implementation of the iconic photo spots. In its implementation, the focus group with the manager plays the leading role because the manager provides directions for the location to be added to the iconic photo spot. Community service contributes in the form of physical development of photo spots in the form of iconic main gates, iconic love lights, and iconic life circles. This activity provides conclusions: the number of tourists visiting is increasing, and the prestige of these tourist attractions will be increasingly famous on social media, especially among the millennial generation.